PENGARUH REBUSAN DAUN UBI JALAR (IPOMOEA BATATAS) TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS TIRON KABUPATEN KEDIRI: The Effect Of Sweet Potato Leaf Stew (Ipomoea Batatas) On Hemoglobin Levels In Pregnant Women In The Work Area Of The Tiron Health Center, Kediri Regency (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2021)
Anemia is a condition.where the hemoglobin level is below normal. Anemia that occurs in pregnant.women is closely related to maternal and infant mortality and morbidity, risk of abortion and IUFD, low birth weight and premature babies. The initial survey conducted in the Tiron Health Center working area in the period June-July 2019 from pregnant women, (60%) pregnant women experienced anemia and (40%) normal, this shows that anemia is still incidence in the working area of ??the Tiron Puskesmas, Kediri Regency. The purpose of this study was to analyze the effect of sweet potato leaf stew on hemoglobin levels in pregnant women. This study was a quasi-experimental study, with One Group Pre-test and post-test design by giving boiled sweet potato leaves for 7 days. The sampling technique used total sampling. The subjects of this study were pregnant women with hemoglobin levels if Trimester 2 <10.5 g / dl and if Trimester 3 <11 ??g / dl. This research was conducted in the working area of ??the Tiron Public Health Center, Kediri Regency. Test analysis using paired T-Test. The results of the paired T-Test analysis showed that the p value was 0.000 or p value <0.05, which means that there was an effect of sweet potato leaf decoction on hemoglobin levels in pregnant women with the average difference in hemoglobin levels before and after treatment of 1.418gr / dl. that the effect of sweet potato leaf decoction on hemoglobin levels in pregnant women can be used as an alternative to increasing hemoglobin levels of pregnant women